(3efjI GdQGZH aj TQM HZjI GdWGdHs - (3GdLfGMj, GdfLaj, ehSi Hf LYaQ cGTa GdZWGA, J (B1243(3g`s
(3ChdgG (B:s
(3GdMeO ddg Pj GdLdGd hGdEcQGe(B... (3hHYO agPg LedI ef GdeSGFd hfHPI ef GdaQhY hGdOdGFd(B...s
(3BNQgG (B:s
(3adG JQaY GdjOjf hbd KdGK eQGJ(B: (3HSe Gddg GdQMef GdQMje (B... (3hdh Yed YdjgG aEfeG jbJUQ (B... (3Je GdLRA GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B: (3L(B23(3, U(B126(3, Qbe(B8643s
(3GdPQjYI(B: (3L(B23(3, U(B126(3, Qbe(B8643s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis